Nanorobots in Medicine-A New Dimension in Bio Nanotechnology - Narayana Rao, Venkat (Discoveries in Agriculture and Food Sciences, 2014)
Bio-nanotechnology has become a hopeful area of research that is bringing radical advancements and changes in the current century of technological mutiny. It is a one part of Nano technology. It has shown its clear participation in all fields, there is an integral part of the nanos in human science and medicine. Nanomedicine is the process of diagnosing cancers, treating, preventing disease, relieving pain, and of preserving and improving human health using molecular tools and molecular knowledge of the human body. Most of the symptoms such as fever and itching have specific biochemical reasons that can also be controlled, reduced, and eliminated using the appropriate injected nanorobots. This paper mainly concentrates on reviewing role and implementation of nano robots in medical field and how it can replace present medical scenarios with cost reduction along with vision to permanent solutions to many human aliments towards surgery less treatments.